Artisanal colombian coffees the third wave - Calle Cuartas, Jhon William (Lupa empresarial, 2018)
Coffee has been traded since the XIV century between Muslim people. It arrived in Europe around the XVII century, and it subsequently came to South America in 1.714, when the first co ee farm was established in Dutch Guyana. Finally, the first co ee roots where brought for French people and Jesuit priests to Brazil and Colombia in the XVII century. The first farming was established in the east of Colombia, and the first commercialization of a harvest of 2,560 bags (exported through Cucuta to Venezuela) was registered in 1.835. Santander and Norte de Santander were the first co ee producing regions in Colombia, but the roots were quickly disseminated to central and west regions of the country to regions as Cundinamarca, Antioquia, and Caldas (also known nowadays with Risaralda and Quindío as El Eje Cafetero, i.e. the co ee hub). In the second half of the XIX century, this item became more relevant as an exporting product due to the expansion of the world economy in this period. The United States of America became the most important coffee market in the world, and at the end of the XIX and the beginning of the XX century the production grew from 60.000 to 600.000 bags. Similarly, international prices and producers’ profits plummeted dramatically in the same period of time. Co ee production grew importantly between 1905 and 1935, and Colombia became the second world producer of co ee. By 1927, producers created the National Federation of Coffee producers – FNC. This Agency was in charge of supporting co ee growers, as well as developing the marketing strategy to promote internationally the product as a brand in a market dominated by Brazil.